Adhesive supramolecular polymeric materials constructed from macrocycle-based host–guest interactions. (23rd April 2019) - Ji, Xiaofan; Ahmed, Mehroz; Long, Lingliang; Khashab, Niveen M.; Huang, Feihe; Sessler, Jonathan L.
Abstract : This review describes recent progress in adhesive supramolecular polymeric materials constructed from macrocycle-based host–guest interactions. Abstract : Nature uses the power of non-covalent interactions as the basis for many kinds of adhesion phenomena. Inspired by nature, scientists have prepared various synthetic adhesive materials that rely on a number of non-covalent interactions at the interfaces. Commonly used non-covalent interactions include hydrogen bonding, π–π stacking, charge transfer interactions, electrostatic interactions, hydrophobic interactions, macrocycle-based host–guest interactions, among others. Within this context, macrocycle-based host–guest interactions are of particular interest. Often they give rise to distinct properties, such as multiple combined noncovalent interactions and a diversity of stimuli-based responsiveness. In this tutorial review, we will summarise recent advances in adhesive supramolecular polymeric materials that rely primarily on macrocycle-based host–guest interactions. An overview of future challenges and a perspective of this sub-field are also provided.